Obstacles and Preventions of Drug Related Problems - AReview - CW, Shashikala; MS, Ganachari; T, Praveen; RB, Prakash; S, Tarang; SS, Geetanjali (Indian Journal of Pharmacy Practice)
Drugs are important in prevention and treatment of disease and health complaints. The increasing number of available drugs and drug users as well as more complex drug regimens led to more side effects and drug interactions, and complicates follow-up. There are different classifications of Drug Related Problems (DRPs) with different focus. Both documenting and classifying DRPs are essential to improve the process of medication's use. DRPs are relatively common in hospitalised patients and can result in patient morbidity and mortality, and increased costs. Problems related to drug therapy may be averted by preventive interventions. Several possibilities for prevention exist, especially for the prevention of medication errors. Prescribing, transcription and interpretation errors can be reduced by using computerised physician order entry. Divided drug related problems in hospitalised patients are mainly divided into two categories: extrinsic drug related problems and intrinsic drug related problems. Some measures to avoid DRPs are the avoidance of look-alike packages, education of personnel involved in the drug distribution process and introducing systems for early detection of adverse drug events. Early detection is important in the prevention of adverse drug reactions and thus each hospital should have a system for the detection of adverse drug reactions. Identifying risk factors that contribute to the development of adverse drug reactions, may also aid in the prevention of these reactions, although the effect of a focus on risk factors is likely to be smaller than the effect of a focus on medication systems improvements.
Keywords: Prevention; Prescribing; Transcription; Interpretation